The Possibilities of Optimization of the Steel Coil Inventory in the Processing Company - Vlčková, Vladimíra; Machač, Otakar (TANGER, spol. s r.o., 2016)
The paper is dedicated to the problems of optimization of the inventory of steel coils in a processing company supplying the B2C market. It aims to describe and analyse the possibilities and barriers of inventory optimization with respect to the linkages with coil suppliers within the supply chain in metallurgy. The conducted targeted scientific literature review focussed on inventory optimization models resulted in selection and application of a modification of the standard Q – model, altered for the particular conditions of the solved problem, which is described and evaluated in the article.
Možnosti optimalizace zásob ocelových svitků ve zpracovatelském podniku
Keywords: optimization; inventory; supply chain; steel coil; optimalizace; zásoby; supply chain; ocelové svitky